Characterization of the key aroma compounds in Chinese JingJiu by quantitative measurements, aroma recombination, and omission experiment. (1st August 2021) - Sun, Xizhen; Du, Jiawei; Xiong, Yaqing; Cao, Qianwen; Wang, Zhe; Li, Hongjun; Zhang, Fan; Chen, Yanhe; Liu, Yuancai
Graphical abstract: Characterization of the key aroma compounds in Chinese JingJiu by quantitative measurements, aroma recombination, and omission experiment. Highlights: This study is pioneer in characterizing the key aroma compounds of Chinese Jingjiu . AEDA and GC–MS show that Chinese Jingjiu contains about 136 volatile compounds. Molecular sensory analysis showed that 43 components are aromatic compounds. Thirteen compounds were confirmed to be the key aroma-active compounds in Chinese Jingjiu . Abstract: The unique flavor of and rich physiological activities exhibited by the Chinese JingJiu has made it become an essential part of the blended alcoholic beverage. In this study, the aromatic characteristics of Chinese JingJiu have been identified using sensory analysis, aroma extraction dilution analysis (AEDA), and quantitative analysis techniques. The odor activity values (OAVs) were also used to characterize the compound. A total of 136 aroma compounds were identified through the AEDA and gas chromatography-mass spectrometry (GC–MS) techniques. The flavor dilution (FD) factors were found to be in the range of 2–1024. Seventy aroma-active compounds with FD ≥ 8 were identified. Forty-three aroma-active compounds were identified using the molecular sensory science approach. Furthermore, 13 compounds were confirmed to be the key aroma-active compounds present in the Chinese JingJiu . The work provides a certain guiding effect on the regulation and optimization of the Chinese JingJiu production process.